RANCANG BANGUN APLIKASI GAME DENGAN TEMA BUILDING ON FIRE BERBASIS VIRTUAL REALITY - Dian Gustina; Muhammad Abi Maulana (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2020)
Technology is one part that can not be separated from human life. Various fields in human life have been greatly aided by the existence of technology, especially computer technology. Virtual Reality (VR) is a new way to explore the virtual world. With virtual reality, penguuna seems to be entering a new environment in a virtual world. The vastness of the virtual world can provide many opportunities to produce a variety of fun entertainment games. "Building On Fire" is a game with an action genre that can be played by all people ranging from children to adults, this game is enough to suppress the sensation for the players, because to win this game we are required to find a way out of a building that has burned down. This application was created using Unity 3D and SDK as the main software. Stages in this study include the identification of problems, initial planning, design and design, testing and implementation. And for system modeling languages using UML (Unified Modeling Language). This application was created as a medium of entertainment for the public by using virtual reality (VR) which aims to enable players to feel more real emotions as if they were in a game and introduce virtual reality technology. System testing shows that not all Samsung smartphones can run this virtual reality game, and also on the application quality test shows that the assessment of this application has a weighting rating of 38.6 which is in the category of "good".Â Keywords : Virtual reality, Android, Unity3D, GameÂ